ISLAMIC ECONOMIC REVIEW ON CIGARETTE BUSINESS SALES - Syarifuddin Syarifuddin; Nurfiah Anwar; Sri Wahyuni (Universitas Islam Negeri Mataram, 2020)
This study aims to examine the Islamic economy, specifically relating to the sale of the cigarette trade. The method used in this study is a literature review, by collecting data from the literature and other sources that support and relate to the discussion in this study. This study also uses analytic methods, including comparative methods, namely analyzing data by comparing one opinion with another, then drawing conclusions so that similarities and differences emerge in the current discussion. The results showed that smoking in the perspective of Islamic economics is an action that is contrary to the concept of maqasid sharia, concerning psychological protection, that is reason, wealth, and life. When smoking is very dangerous for yourself and others. So they produce, buy, and sell them as perpetrators of damage on earth. In fact, creating danger is tantamount to eliminating Sharia in body, mind, and property.